The impact of environmental factors on the immunopathogenesis of osteoporosis: A systematic review - Prabowo Nurhasan Agung; Soetrisno; Nurwati Ida; Ardyanto Tonang Dwi; Poncorini Eti; Nurudhin Arief; Dirgahayu Paramasari (BIO Web of Conferences)
Osteoporosis is a metabolic bone disease predominantly driven by environmental variables that damage bone microarchitecture and increase the risk of fractures. This systematic study analyzes environmental variables' impact on osteoporosis immunopathogenesis. We identified studies investigating the relationship between air pollution, heavy metal exposure, and chemical exposure with immune activity in osteoporosis through searches in PubMed databases. The review's findings indicate that exposure to environmental pollutants triggers systemic inflammation and oxidative stress, contributing to an imbalance between bone formation and resorption. Fine particulate matter (PM2.5) and nitrogen dioxide (NO2) pollutants are linked to reduced bone mineral density and a heightened risk of osteoporosis. This study underscores the importance of preventive strategies and public health policies that consider reducing environmental pollutant exposure to decrease osteoporosis risk. The results further emphasise the necessity for targeted interventions to safeguard at-risk individuals against the detrimental impacts of environmental variables on bone health.